Organizational culture and leadership - Schein, Edgar H. (San Francisco Jossey-Bass, 2010)
"Regarded as one of the most influential management books of all time, this fourth edition of Leadership and Organizational Culture transforms the abstract concept of culture into a tool that can be used to better shape the dynamics of organization and change. This updated edition focuses on today?s business realities. Edgar Schein draws on a wide range of contemporary research to redefine culture and demonstrate the crucial role leaders play in successfully applying the principles of culture to achieve their organizational goals"
Includes bibliographical references (p. 401-414) and index
Keywords: Corporate culture